8.2 mJ, 324 MW, 5 kHz picosecond MOPA system based on Nd:YAG slab amplifiers. (26th May 2016) - Chen, Ying; Liu, Ke; Yang, Jing; Yang, Feng; Gao, Hong-wei; Zong, Nan; Yuan, Lei; Lin, Yan-yong; Liu, Zhao; Peng, Qin-jun; Bo, Yong; Cui, Da-fu; et al.
Abstract: We have demonstrated a high pulse energy, high peak power, and high beam quality picosecond (ps) master oscillator power amplifier system of 1064 nm at a pulse repetition rate of 5 kHz. This system consisted of a ps mode-locked oscillator, a regeneration amplifier, and three-stage Nd:YAG slab amplifiers, which enabled us to manage good thermal issues and provide an average power of 41 W. Up to 8.2 mJ of energy per pulse was achieved at the total absorbed pump power of 460 W with an average extraction efficiency of 8.5%. The pulse duration was 25.3 ps, which corresponds to a peak power of 324 MW. The beam quality factors of M 2 were measured to be M x 2 = 2.8 along the x axis direction and M y 2 = 2.2 along the y axis direction, respectively, and the corresponding brightness was as high as 5.88 × 10 8 W cm −2 · Sr.